COMPARATIVE ANALYSIS OF THE LEGAL VALUE AND IMPORTANCE OF PREAMBLES OF CONSTITUTIONS: THE POSSIBILITY OF BEING AN EXAMPLE OF THE CROATIAN CONSTITUTIONAL PREAMBLE IN RELATION TO THE MACEDONIAN CONSTITUTION - Körbayram, Azam (International Scientific Journal Vision, 2023)
In a period that is preparing for constitutional changes in North Macedonia, especially in the part of the preamble, we received the opinion that there is a need for a detailed analysis of the subject, which will be researched the legal framework and the importance of the preamble, then through the prism of comparative analyzes of preambles and court decisions on the same (both constitutional judiciary and supreme courts) of different European countries, and finally a separate comparison of the preamble of Croatia, which is considered one of the most liberal-democratic models on the European continent, and the preamble of North Macedonia as a candidate member of the EU, especially due to the fulfillment of the Copenhagen criteria, one of which is respect for minorities,. With used literature from more than four languages and formats of scientific works, elements or legal changes that would be necessary for the constitution or the democratization of the constitutional order of the Republic of North Macedonia will be proposed.